Strength training to improve performance in athletes with cerebral palsy: A systematic review of current evidence - Fleeton, J. R.; Sanders, R. H.; Fornusek, C. (The Journal of Strength and Conditioning Research, 2020)
Persons with cerebral palsy (CP) can partake in many different forms of organized sport including elite competition at state and international levels. There is limited evidence on how CP athletes should train to enhance performance. The purposes of this article were to conduct a systematic review of the current evidence on ambulatory individuals with CP for (a) strength and functional improvement through strength training; (b) potential sports performance improvement through strength training; (c) the identification of risk and special considerations associated with strength and conditioning for this population, and; (d) the identification of future research foci to educate strength and conditioning coaches on specific program design for elite CP athletes. Seven electronic databases were searched for studies investigating resistance training interventions. The databases were also searched for training interventions or investigations into sports performance in athletes with CP competing at regional level or above. Thirty articles were included in the systematic review of strength training, and 23 articles included in the narrative review of training for sports performance. High-quality evidence indicates that resistance training can improve muscular strength in individuals with CP, with some preliminary evidence of structural and neurological adaptations. However, there is limited evidence for functional improvements. Limited research has examined the performance capacity of athletes with CP, and no training interventions have been conducted. Coaches should employ existing guidelines when designing programs while considering specific athlete limitations. Initially, the focus should be increasing athlete muscular strength before considering specific sport demands.